Analisis Pengaruh Kinerja Keuangan Terhadap Harga Saham (Studi Pada Perusahaan Sub Sektor Farmasi Yang Terdaftar Di Bursa Efek Indonesia Tahun 2014 – 2018) - Jati Satrio; Achmad Suhaili (Universitas Lambung Mangkurat, 2022)
ABSTRACT In this study, the aim is to obtain evidance regarding the analysis of the effect of finansial performance on stock prices. The independent variable used in this study is Current Ratio, Return on Equity, Debt to Equity Ratio and Total Assets Turnover. While the dependent variable used in this study is the share price measured using Moving Average 200 (MA200).The population in this study is all pharmaceutical sub-sector manufacturing companies that have been listed on the Indonesia Stock Exchange in the 2014 – 2018 period. In determining the sample of this study using the purposive sampling method and has obtained a sample of 7 pharmaceutical sub-sector manufacturing companies based on predermined criteria. The analysis technique used in this study isu sing multiple regression analysis through SPSS version 26.The result of this study indicate that: (1) Current Ratio has no influence on stock prices, (2) Return on Equity has a positive and significant effect on stock prices, (3) Debt to Equity Ratio has no influence on stock prices, (4) Total Assets Turnover has a positive and significant effect on stock prices. Keywords: Stock Price, Current Ratio, Return on Equity, Debt to Equity Ratio and Total Assets Turnover